Effects of Aging on the Changes of Respiration during Swallowing - SUGIMOTO, Sukeo; KAMAKURA, Yayoi; FUKADA, Junko (The Japanese Journal of Dysphagia Rehabilitation, 1998)
As a basic study to develop the technique to take care of the elderly patients with the difficulty in swallowing，we investigated the effects of aging on the changes of respiration during swallowing. The subjects swallowed 10 ml of water of the room temperature and their respirograms and surface electromyograms （EMGs） of the suprahyoid muscles were simultaneously recorded. The subjects who understood the purpose of the present study and expressed their consent classified into the following three groups： young group （n＝20，mean age 19.5 ± 2.7 years）， presenile group （n＝10， mean age 64.8 ± 3.2 years） and senile group （n＝17， mean age 85.6 ± 2.9 years）. Their respiration patterns during swallowing were classified and the frequency of each pattern was calculated. Furthermore these three groups were compared with one another as to the frequency of respiration pattern， the resting respiratory cycle and the duration of deglutition apnea. EMGs of the suprahyoid muscle activity were also compared between the young group and the senile group. The respiration pattern was classified into two types， each of which comprised three subtypes： subsequent expiration type （eae， ae and iae subtypes） and subsequent inspiration type （eai， ai and iai subtypes）． Although the frequency of the eae subtype （expiration-apnea-expiration） was the highest in all the three groups， the result of the senile group （42.6％） was significantly lower than the results of the young group （60.5％）and the presenile group （64.3％） （P＜0.05）. The duration of respiration cycle was 4.39 ± 1.10 sec in the young group， 3.50 ± 0.63 sec in the presenile group and 2.95 ± 0.44 sec in the senile group. This indicated that the duration significantly decreased with the increase in age （P＜0.01）. The duration of deglutition apnea was 0.94 ±0.20 sec in the young group， 1.02 ± 0.20 sec in the presenile group and 1.36 ± 0.46 sec in the senile group. This indicated that the duration in the senile group significantly increased （P＜0.01）. Regarding the muscle activity，the interval between the muscle contraction starting point and the peak EMG point and the interval between the muscle contraction starting point and the apnea starting point showed the significant increase in the senile group （P＜0.01）. ln the young group， the peak EMG was achieved 0.04 ± 0.08 sec after the onset of apnea and the coincidence between the apnea starting point and the peak EMG was recognized. ln the senile group，the achievement of the peak EMG was significantly delayed and observed 0.26 ± 0.30 sec after the onset of apnea. Although the average result of electromyography and the integrated result significantly increased in the senile group， no remarkable difference in the peak EMG point was recognized between the two groups. These results suggested that the respiration pattern during swallowing and the duration of deglutition apnea changed with the increase in age.